FRI0103 The Omeract Preliminary Flare Questionnaire (PFQ) is Responsive to Change and Able to Detect Clinically Important Worsening Indicating Need for Treatment Change in the Canadian Early Arthritis Cohort. (10th June 2014) - Bykerk, V.P.; Bingham, C.O.; Choy, E.H.; Boire, G.; Haraoui, B.P.; Lin, D.; Pope, J.E.; Thorne, J.; Hitchon, C.; Tin, D.; Keystone, E.C.; Bartlett, S.J.
Abstract : Background: Rheumatoid arthritis (RA) flares are common, poorly defined, and understudied. A new tool is being developed that can measure significant inflammatory RA flares that may signal need for treatment change. Qualitative and quantitative research by the OMERACT RA Flare Group with an international group of scientists, patients (pts) and healthcare providers has led to identification of an RA Flare Core Domain Set ratified by OMERACT 2012 attendees. Objectives: To evaluate the responsiveness of the OMERACT Preliminary Flare Questionnaire (PFQ) to changes in flare status defined using four criteria in a large early RA observational trial. Methods: 501 pts in CATCH (Canadian early ArThritis CoHort) completed PFQs at 2 consecutive visits from 11-2011 through 5-2013. Flare status was classified using rheumatologist (MD) and pt evaluations as well as two proposed DAS28-based criteria (one more sensitive, one more specific). The PFQ asks pts to rate their pain, function, fatigue, stiffness, participation and coping over the prior week using 11-point NRS scales. Inter-rater reliability for flare status was assessed by % agreement (kappa). Mean differences and effect sizes in PFQ scores were compared between pts who changed to flare status at the 2nd visit vs. pts whose status remained the same but not improved. Results: At enrollment, pts were female (75%), white (83%), and 59% had > HS education. Mean (SD) age was 55 (15) years and RA duration 6 (3) months. Using MD evaluations, 148 pts (30%) changed to a flare status at the 2nd visit; 124 (25%) were classified using patient report, while only 38 (8%) and 58 (13%) changed status using the specific and sensitive DAS criteria. Inter-rater reliability regarding flare status was 74% (Kappa 0.34) between MD and pt evaluations, but was lower with the most specific DAS criterion (72% (Kappa.17). NSAIDs, steroids, and DMARDs use increased with change to flare status. Irrespective of flare classification used, in each PFQ domain, mean scores changed significantly in flare pts; conversely, PFQ domain scores over 2 visits were stable in pts whose flare status was unchanged (Table). Conclusions: These data suggest the PFQ is responsive to clinically meaningful changes in inflammatory flare status in pts with early RA using 4 different flare classifications. Physician evaluations resulted more pts being reclassified, followed by patient evaluation; DAS criteria resulted in fewer patients being reclassified, suggesting this approach is relatively insensitive to change. These results from a large national observational study increase confidence in OMERACT PFQ's ability to detect clinically meaningful change in inflammatory flare status over time in early RA. Additional psychometric evaluation is needed to establish the reliability, validity, and responsiveness of the PFQ and relevant thresholds across a range of RA populations and settings prior to widespread use. Acknowledgements: The CATCH study was designed and implemented by the investigators and financially supported initially by Amgen Canada Inc. and Pfizer Canada Inc. via an unrestricted research grant since the inception of CATCH. As of 2011, further support was provided by Hoffmann-LaRoche Ltd., UCB Canada Inc., Bristol-Myers Squibb Canada Co., AbbVie Corporation (formerly Abbott Laboratories Ltd.), and Janssen Biotech Inc. (a wholly owned subsidiary of Johnson & Johnson Inc.) Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.4489